(untitled) (Journal of University of Babylon for Engineering Sciences, 2018)
Solar distillation is an effective and a useful method to solve the problem of water scarcity usable on the surface of the earth. A multi-stage solar still was used, and the performance of it was improved by linking it to (Evacuated Solar Collector Tubes), the rate of increase in productivity is about (38%). Practical and theoretical calculations were carried out on two cases. The first case was the basin of the first stage containing water only; the second case was the basin containing the fiber of the palm. When comparing the two cases there was a similarity between the two cases, but the addition of leaf fiber improved the increase in night productivity. The rate of increase in night productivity is about (25%).This type of solar still was a modern technology in improving the performance of multi-stage solar still.